THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION, DIGITAL ENTREPRENEURSHIP AND GENDER ON ENTREPRENEURIAL INTEREST - Auliadara, Nurul; Sojanah, Janah; Purnamasari, Imas (Jurnal Pendidikan Ilmu Sosial, 2024)
This study focuses on the Influence of Entrepreneurship Education, Digital Entrepreneurship and gender on students' interest in entrepreneurship at the Geology and Mining Polytechnic "AGP" Bandung. Based on the employment challenges faced by diploma III graduates, especially in terms of unemployment, and the important role of entrepreneurship as a solution to create new jobs. The purpose of this study was to determine the influence of entrepreneurship education, digital entrepreneurship and gender on entrepreneurial interest. The theory used is the Theory of Planned Behavior from Ajzen, 1991. The population was 207 students, the sample used was 136 students of the Geology and Mining Polytechnic "AGP" Bandung. Data were collected through Questionnaires and analysis using PLS-SEM. The results showed that entrepreneurship education did not have a significant effect on students' interest in entrepreneurship; digital entrepreneurship has a positive and significant effect on students' interest in entrepreneurship; and gender does not have a significant effect on students' interest in entrepreneurship. It is recommended that entrepreneurship education be developed from the learning process and entrepreneurial skills taught in order to build and strengthen students' interest in entrepreneurship to become successful entrepreneurs in the digital era.